PEMBERHENTIAN DIREKSI SECARA MELAWAN HUKUM BERDASARKAN UU NO.40 TAHUN 2007 TENTANG PERSEROAN TERBATAS: Unlawful Dismissal Of Directors Based On Law No.40 Of 2007 Concerning Limited Liability Companies - Apriyanto, Zaeriko Rizky; Kerti, N.G.N Renti Maharaini (Faculty of Law, Universitas Trisakti, 2024)
The board of directors is a key component of a company responsible for overseeing its operations andrepresenting it both in and out of court. The board can be removed at any time through a GeneralMeeting of Shareholders (RUPS) resolution, citing specific reasons for their removal. This study delvesinto the validity of PT. Multi Daya Wonua's RUPS regarding director dismissal. It also examineswhether the decisions in Case Number 16/pdt.G/2019/PN Kka, 82/PDT/2019/PT KDI, and 1888K/pdt/2020 on director dismissal at PT. Multi Daya Wonua align with the guidelines set out in LawNumber 40 of 2007 concerning Limited Liability Companies. The research follows a normative legalapproach, utilizing descriptive-analytical methods to review existing materials and offer insights throughcollected data. The study primarily employs qualitative analysis of secondary data. Findings highlight that removing directors without specifying reasons through RUPS and without allowing a defensecontradicts Article